Reforms in the Field of Oil and Gas Industry in the Republic of Uzbekistan - Ismoilov Sunnatillo Isoqovich (International Journal on Integrated Education, 2022)
The development of the oil and gas industry during the years of independence, carried out by the government in the event of one of the most important directions of cooperation on the basis of mutually beneficial relations with foreign countries and companies consist of the form of network. Should be noted that, or the government of the republic and the state of the development of cooperation with foreign companies primarily in the stocks of raw materials, mainly proceeding from national interests rendered most of the activities to identify, search, extraction as well as processing power increases was paid to go. For the same purpose today, to identify the sources of raw materials, oil and gas, search and find the most modern technology and experience in mining companies that have established cooperation with a number of advanced facilities. As a result, the ongoing financial and economic crisis at the international level of foreign companies in uzbekistan in the conditions of the current period, with a number of promising projects are being implemented. Cooperation with foreign companies to be established in order to strengthen the economy of the country conducted by the industry, the importance of the implementation of drastic reforms in foreign investment have been included to the ground that has been created. In this article reforms carried out in the Republic of Uzbekistan in the field of oil and gas industry and contains information about the results of their stage.